FVR, Sin, Erap, Jawo & other peeves - Yuson, Alfred A. (Pasig City : Anvil Pub, 1997)
"The essays in this collection first appeared in The Manila Chronicle, Philippines Graphic, Philippine Daily Inquirer, The Evening Paper and ISYU".
Keywords: Philippines -- Politics and government -- 1986-